Two new species of the genus Podalonia Fernald from China and a key to the Chinese species of the genus (Hymenoptera: Sphecidae) - Wang, Chun-Hong; Li, Qiang; Ma, Li (Zootaxa, 2016)
Two new species are described: Podalonia arcuaticlypeata Wang & Ma, sp. nov. from Xinjiang, China and Podalonia bicellularis Wang & Ma, sp. nov. from Qinghai, China. A key to the species of Podalonia from China is provided.